A Study on the Impact of Timing Schedule on the Performance of Employees: Enhancing Organizational Productivity through Flexible Work Hours (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Flexible working hours are very important for those organizations who are working on 24 hour basis. Such organizations can hire trained, skilled and experienced work force by implementing this Flexi hours (timings) schedule, so that such workers can work in more than one organization on a day and more than one organization can get benefit by these organizations. And it is also helpful for the organizations which don’t have enough space for the workforce but the want to work more and produce more. Such organizations can manage all this by implementing flexible work hours. Many other problems such as administrative problems can be handled properly by ensuring flexible work hours.